MicroRNAs promote skeletal muscle differentiation of mesodermal iPSC-derived progenitors. Issue 1 (December 2017) - Giacomazzi, Giorgia; Holvoet, Bryan; Trenson, Sander; Caluwé, Ellen; Kravic, Bojana; Grosemans, Hanne; Cortés-Calabuig, Álvaro; Deroose, Christophe M.; Huylebroeck, Danny; Hashemolhosseini, Said; Janssens, Stefan; McNally, Elizabeth; et al.
Abstract Muscular dystrophies (MDs) are often characterized by impairment of both skeletal and cardiac muscle. Regenerative strategies for both compartments therefore constitute a therapeutic avenue. Mesodermal iPSC-derived progenitors (MiPs) can regenerate both striated muscle types simultaneously in mice. Importantly, MiP myogenic propensity is influenced by somatic lineage retention. However, it is still unknown whether human MiPs have in vivo potential. Furthermore, methods to enhance the intrinsic myogenic properties of MiPs are likely needed, given the scope and need to correct large amounts of muscle in the MDs. Here, we document that human MiPs can successfully engraft into the skeletal muscle and hearts of dystrophic mice. Utilizing non-invasive live imaging and selectively induced apoptosis, we report evidence of striated muscle regeneration in vivo in mice by human MiPs. Finally, combining RNA-seq and miRNA-seq data, we define miRNA cocktails that promote the myogenic potential of human MiPs. Mesodermal iPSC-derived progenitors (MiPs) can regenerate both skeletal and cardiac muscle. Here, the authors show that a microRNA cocktail stimulates skeletal muscle differentiation and that human MiPs can engraft into striated muscle in mice.